2020
DOI: 10.2147/ce.s203634
|View full text |Cite
|
Sign up to set email alerts
|

<p>Management of Chemotherapy-Induced Nausea and Vomiting (CINV): A Short Review on the Role of Netupitant-Palonosetron (NEPA)</p>

Abstract: Introduction Antineoplastic drugs may induce several side effects, including chemotherapy-induced nausea and vomiting (CINV). Two neurotransmitters play a central role in mediating the emetic response: serotonin acting on the 5HT3 receptor and the substance P targeting the NK1 receptor. Indeed, a combination of a 5HT3 receptor antagonist (5HT3-RA) and a NK1 receptor antagonist (NK1-RA) together with dexamethasone has been shown to be very effective. In fact, this combination is actually widely use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…33 Although a high dose of radiation has been shown to disrupt the BBB, 65 our imaging and functional studies revealed that 5 Gy radiation therapy enhanced transportation of SLN to glioblastomas and led to an increase in therapeutic effect and mouse survival. Targeted SLN through iRGD showed the most therapeutic effect in preirradiated mice (as compared to nontargeted SLN, or targeted SLN with no radiation), despite previous studies claiming that active targeting does not show drastic improvement, [66][67][68] and proving further that the observed effect is not due to potential BBB disruption by radiation. Hence, combining nanoparticle-based targeted delivery systems with radiation may lead to promising therapy in a clinical setting.…”
Section: Discussionmentioning
confidence: 81%
“…33 Although a high dose of radiation has been shown to disrupt the BBB, 65 our imaging and functional studies revealed that 5 Gy radiation therapy enhanced transportation of SLN to glioblastomas and led to an increase in therapeutic effect and mouse survival. Targeted SLN through iRGD showed the most therapeutic effect in preirradiated mice (as compared to nontargeted SLN, or targeted SLN with no radiation), despite previous studies claiming that active targeting does not show drastic improvement, [66][67][68] and proving further that the observed effect is not due to potential BBB disruption by radiation. Hence, combining nanoparticle-based targeted delivery systems with radiation may lead to promising therapy in a clinical setting.…”
Section: Discussionmentioning
confidence: 81%
“…This suggests that TRPV1-mediated CGRP and SP release from nerve terminals play a role in emesis [ 53 ]. NK1-receptor antagonists have been successfully used along with 5-HT3-receptor antagonists to treat chemotherapy-induced emesis [ 183 , 184 ]. Morphine and 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT) act as antiemetics [ 185 ].…”
Section: Role Of Trpv1 In Cannabinoid-induced Antiemesismentioning
confidence: 99%
“…6 On September 28, 2017, Health Canada issued a Notice of Compliance for netupitant/palonosetron (NEPA) -a combination of a highly selective NK 1 RA netupitant (300 mg) and palonosetron (0.5 mg) -in combination with DEX, for once-per-cycle treatment in adult patients for the "prevention of acute and delayed nausea and vomiting associated with HEC and prevention of acute nausea and vomiting associated with MEC therapy that is uncontrolled by a 5-HT 3 RA." 7,8 Over the past decades, the development of new antiemetic drugs has progressed and shown promising results in the prevention of CINV. Particularly, the appearance of second-generation of 5-HT 3 receptor palonosetron and its combination with netupitant in NEPA has urged a literature review on the clinical effectiveness and cost-effectiveness of these drugs relative to other 5-HT 3 RAs.…”
Section: Context and Policy Issuesmentioning
confidence: 99%